Still engaged - healthcare staff's engagement when introducing a new eHealth solution for wound management: a qualitative study - Cecilia Fagerström; Hanna Wickström; Hanna Tuvesson (BMC, 2022)
Abstract Background eHealth solutions have often been considered favourable for improved effectiveness and quality in healthcare services for wound management. Staff engagement related to organisational changes is a key factor for successful development and implementation of a new eHealth solution, like a digital decision support systems (DDSS). It is essential to understand the engagement process in terms of sustainability, wellbeing in staff and efficiency in a long-term perspective. The aim of this study was to describe healthcare staff's engagement during a 6-month test of an eHealth solution (DDSS) for wound management. Methods A qualitative design, including interviews conducted with healthcare staff working with wound management within primary, community and specialist care (n = 11) on two occasions: at the introduction of the solution and after 6 months, when the test period was over. Data were interpreted with qualitative content analysis. Results Healthcare staff's descriptions from a 6-month test of an eHealth solution for wound management can be summarised as Engaging through meaning, but draining. The analysis revealed a result with three subcategories: Having a shared interest is stimulating, Good but not perfect and Exciting, but sometimes exhausting. The staff described their engagement as sustained through feelings of meaningfulness when using the eHealth solution, but limited by feelings of exhaustion due to heavy workload and lack of support and understanding from others. Conclusions The results indicate that the healthcare staff who tested the eHealth solution described themselves as individuals who easily become engaged when an idea and efforts felt meaningful. The staff needed resources to nourish engagement in their new role when implementing eHealth in the clinical everyday work of wound management. Allocating time and support are important to consider when planning for sustainable implementation of eHealth solutions in healthcare organisations.